2022
DOI: 10.1002/stc.3143
|View full text |Cite
|
Sign up to set email alerts
|

Robust optimal sensor configuration using the value of information

Abstract: Sensing is the cornerstone of any functional structural health monitoring technology, with sensor number and placement being a key aspect for reliable monitoring. We introduce for the first time a robust methodology for optimal sensor configuration based on the value of information that accounts for (1) uncertainties from updatable and nonupdatable parameters, (2) variability of the objective function with respect to nonupdatable parameters, and (3) the spatial correlation between sensors. The optimal sensor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Using utility theory [40], the optimal experimental design is accomplished by maximizing the expected information gain over all possible data generated from the prediction error model. It can be shown that asymptotically for large number of data and small prediction errors, the utility function that measures the expected information gain from the data can be simplified as follows [41,42,43,30]…”
Section: Information Gain From a Sensor Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using utility theory [40], the optimal experimental design is accomplished by maximizing the expected information gain over all possible data generated from the prediction error model. It can be shown that asymptotically for large number of data and small prediction errors, the utility function that measures the expected information gain from the data can be simplified as follows [41,42,43,30]…”
Section: Information Gain From a Sensor Configurationmentioning
confidence: 99%
“…Leyder et al [28] reported on optimal sensor configurations for the modal identification of a post-tensioned timber frame structure while keeping the number of necessary sensors to a minimum. More recently, a methodology for optimal sensor configuration based on the value of information was reported in [29,30], while Ercan et al [31,32] presented information entropy based optimal sensor placement strategies for virtual sensing. A thorough review of the different optimal sensor placement strategies for SHM applications can be found in [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the enhanced particle swarm optimization algorithm, the system iteratively seeks the optimal solution for the data set, which corresponds to the solution of the cluster center. Once the cluster center was determined, data points were assigned to the nearest cluster based on the nearest neighbor distance, calculated as shown in Formula (11). The resulting output was the data set's clustering set.…”
Section: Pso-based Three-way K-means Algorithmmentioning
confidence: 99%
“…In step 5, calculate the distances from all samples within each particle to the cluster centers using Formula (11). Following the principle of proximity, assign each sample to the cluster whose center was closest, thereby effectively partitioning them into their respective clusters.…”
Section: Pso-based Three-way K-means Algorithmmentioning
confidence: 99%
See 1 more Smart Citation